Incorporation of poison center services in a state‐wide overdose education and naloxone distribution program. Issue 4 (24th May 2016) - Doyon, Suzanne; Benton, Carleigh; Anderson, Bruce A.; Baier, Michael; Haas, Erin; Hadley, Lisa; Maehr, Jennifer; Rebbert‐Franklin, Kathleen; Olsen, Yngvild; Welsh, Christopher
Abstract : Background: To help curb the opioid overdose epidemic, many states are implementing overdose education and naloxone distribution (OEND) programs. Few evaluations of these programs exist. Maryland's OEND program incorporated the services of the poison center. It asked bystanders to call the poison center within 2 hours of administration of naloxone. Bystanders included law enforcement (LE). Objective: Description of the initial experience with this unique OEND program component. Methods: Retrospective case series of all cases of bystander‐administered naloxone reported to the Maryland Poison Center over 16 months. Cases were followed to final outcome, for example, hospital discharge or death. Indications for naloxone included suspected opioid exposure and unresponsiveness, respiratory depression, or cyanosis. Naloxone response was defined as person's ability to breathe, talk, or walk within minutes of administration. Results: Seventy‐eight cases of bystander‐administered naloxone were reported. Positive response to naloxone was observed in 75.6% of overall cases. Response rates were 86.1% and 70.9% for suspected exposures to heroin and prescription opioids, respectively. Two individuals failed to respond to naloxone and died. Discussion: Naloxone response rates were higher and admission to the intensive care unit rates were lower in heroin overdoses than prescription opioid overdoses. Conclusions: This retrospective case series of 78 cases of bystander‐administered naloxone reports a 75.6% overall rate of reversal. Scientific Significance: The findings of this study may be more generalizable. Incorporation of poison center services facilitated the capture of more timely data not usually available to OEND programs. (Am J Addict 2016;25:301–306)